Independent positioning and action of Escherichia coli replisomes in live cells. - Reyes-Lamothe, R; Possoz, C; Danilova, O; Sherratt, D (2008)
A prevalent view of DNA replication has been that it is carried out in fixed "replication factories." By tracking the progression of sister replication forks with respect to genetic loci in live Escherichia coli, we show that at initiation replisomes assemble at replication origins irrespective of where the origins are positioned within the cell. Sister replisomes separate and move to opposite cell halves shortly after initiation, migrating outwards as replication proceeds and both returning to midcell as replication termination approaches. DNA polymerase is maintained at stalled replication forks, and over short intervals of time replisomes are more dynamic than genetic loci. The data are inconsistent with models in which replisomes associated with sister forks act within a fixed replication factory. We conclude that independent replication forks follow the path of the compacted chromosomal DNA, with no structure other than DNA anchoring the replisome to any particular cellular region.